Development of Android-Based Augmented Reality Learning Media to Improve Learning Independence (Study on the Electric Motor Installation Subject for Class XI Students of Rejang Lebong Regency Vocational School) - Prismar, Prismar; Riyanto, Riyanto; Risdianto, Eko; Chandra, Muhammad Fiqih Rizqi; Macariola, Juli Simon; Farooque, Sm (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
The research aims to develop Android-based augmented reality (AR) media that can increase learning independence, describe the media's suitability, describe the media's practicality, and describe the effectiveness of Android-based Augmented Reality (AR) media in increasing learning independence. The scope of this research is all classes. The type of research is Research and Development approach with the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). Data collection used lifting, observation, interviews, and questionnaires. The data analysis technique is by using quantitative descriptive techniques using a Likert scale to describe trends. The research results show that at the analysis stage, learning media that is interesting, interactive, inspiring, fun, challenging, and encouraging independent learning is needed. At the design stage, Android-based AR media was created. In the development stage, media expert assessment is given very feasible criteria. Criteria subject matter expert is very worthy. Practicality tests by teachers as media users show efficient criteria. Limited scale trials obtained significant differences between the control class (quite independent) and the experimental class (independent) with student responses, strongly agreeing. In the implementation stage, significant differences were obtained between the control class (independent) and the experimental class (very independent) with student responses, strongly agreeing. The evaluation stage ensures that the media is suitable and effective for use. The conclusion is that the developed Android-based augmented reality (AR) media can increase learning independence, is suitable for use, practical in use, and effective in increasing the learning independence of class XI vocational school students in Rejang Lebong district.